Alat Monitoring dan Pemberian Pakan Ikan Otomatis berbasis Arduino Uno R3 - Aggry Saputra; Muhammad Rahmadani Ehma (LPPM Universitas Putera Batam, 2022)
Feed is the main factor in fish cultivation, the main problem faced by rancher is the provision of fish feed which still depends on human resources. The weakness of this system is that feeding is not done regularly, irregular feeding will have an impact on fish growth. The monitoring and feeding system of fish is designed using Arduino Uno R3 microcontroller, ultrasonic sensor, servo motor and SMS Gateway to provide information to rancher. The ultrasonic sensor functions to detect the availability of feed, while the servo motor is used as a driver to remove feed. With the application of monitoring tools and automatic feeding of fish, it is hoped that the feeding of fish will be more regular. This system can feed fish automatically on a scheduled basis and can provide information on feed availability to rancher via SMS.